Theoretical and methodological approaches to the study of customer service geography - Olesya Kornus (Časopis Socìalʹno-Ekonomìčnoï Geografìï, 2014)
The article reviews and analyzes the theoretical and methodological approaches to the study of the customer service sector such as: anthropogeographical, statistical-industrial, integrated and territorial, historical-geographical, social, demographic, sociological, economic-geographical, informational, synergetic, systematical and spacial (horological). It reveals the main features of these scientific approaches and their significance in studying the customer service industry. The highlight is made on the  systematic approach as the priority one in the research  of the customer service industry.